The mental image of the hepatica in modern Lithuanian prose - Gritėnienė, Aurelija (Lietuvių kalba, 2014)
Hepatica (Hepatica nobilis) is a very well-known plant, which is common in Lithuania from early times. The works of art are filled with the images of it. The material for this article was collected from works of fiction and prose of the twenty-first century Lithuanian authors including novels, short stories, novellas, tales and other works of similar genres. The whole text is not analysed but rather separate sentences or their fragments – the collocations of hepatica. The material of this research contains 56 works of 46 prose writers, in which the hepatica is portrayed in various ways and purposes. In the compiled collocations the root žibut-/žibuč was located 76 times and žibuokl-/ was mentioned 40 times. The article investigates, which qualities of this plant rise as the most important ones, in other words, what concept of hepatica develops and how. It is found that in most cases Lithuanian prose writers emphasize on visible features of the plant – the colour and shape of the blossoms, their quality to wilt quickly and the like. The most dominant function of the image of hepatica is to express the idea of spring and because of that the parameters of time and space are used frequently in the collocations of hepatica – the exact time of emergence of the blossoms is defined and the growing places of hepaticas are indicated. The smell and purpose of the plant are also becoming quite significant components. It is ascertained that this plant is mostly depicted as the component of traditional Lithuanian scenery, however beside the domestic, realistic and concrete mental image of the plant it is often possible to identify the secondary meanings of the image as well (hepaticas help to express the state and feelings of a character, they become a symbol of faith and hope). Moreover, in the texts of prose there are plenty of cases when hepatica becomes a proper noun – through the process of onimization this title is transferred with a purpose to name people, domestic animals, streets or cafes.
Keywords: none